A HYBRID ORIGIN FOR THE QIANSHAN A-TYPE GRANITE, NORTHEAST CHINA: GEOCHEMICAL AND SR-ND-HF ISOTOPIC EVIDENCE - Yang J.-H.; Wu F.-Y.; Chung S.-L.; Chu M.-F.; Wilde S.A. (My University, 2006)
Major and trace element, whole rock Sr and Nd isotope and zircon Hf isotope data are reported for a suite of A-type granites and mafic microgranular enclaves from the Early Cretaceous (126 ± 2 Ma) Qianshan pluton, Liaodong Peninsula, northeast China, with the aim of investigating the sources and petrogenesis of A-type granites. The Qianshan pluton includes hornblende alkali-feldspar granite, graphic biotite granite and mafic microgranular enclaves. The hornblende alkali-feldspar granites have high SiO2, Fe2O3T / MgO, K2O + Na2O, Rb, Zr and LREE contents and low Ba and Sr concentrations with strongly negative Eu anomalies. Their high Rb / Sr (87Rb / 86Sr = 16.76-24.15) and initial 87Sr / 86Sr ratios (0.7215 to 0.7283), negative εNd(t) values (- 14.1 to - 16.5) and zircon εHf(t) values (- 18.9 to - 11.5) indicate they were mainly derived from a crustal source, but with involvement of high εNd(t) and εHf(t) materials. Graphic biotite granites have similar geochemical features and Sr-Nd-Hf isotopic compositions to enclaves, indicating they were the result of crystal fractionation of evolved mafic magmas, but with involvement of low εNd(t) and εHf(t) materials. The mafic enclaves have an igneous texture and contain acicular apatite, suggesting quenching of mafic magmas that have co-mingled with the host granites. They have low initial 87Sr / 86Sr ratios (0.7097-0.7148), negative εNd(t) (- 14.5 to - 11.9) and zircon εHf(t) (- 17.1 to - 6.9) values, and are enriched in LILEs and LREEs and depleted in HFSEs. When coupled with the high MgO (Mg# up to 54), this indicates derivation from an enriched lithospheric mantle source, but contaminated by crustal materials. Geochemical and Sr-, Nd- and zircon Hf-isotopic compositions rule out simple crystal-liquid fractionation or restite unmixing as the major genetic link between enclaves and host rocks. Instead, magma mixing of mantle-derived mafic and crustal-derived magmas, coupled with crystal fractionation, is compatible with the data. This example shows that at least some A-type granites formed through a complex process involving mantle- and crustal-derived magma mixing, crystal fractionation and infracrustal melting. © 2005 Elsevier B.V. All rights reserved.
Keywords: A-TYPE GRANITE; MAFIC MICROGRANULAR ENCLAVES; MAGMA MIXING; SR-ND ISOTOPES; ZIRCON HF ISOTOPES; Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая